A dinâmica imperialista contemporânea : capital sem fronteiras e sua (ir)racionalidade apátrida - Lima, Lucas Gama (2015)
The present doctoral thesis aims to reflect on the uniqueness of contemporary imperialism. In the last decades, imperialism as category of analysis, lost centrality in the Marxist analysis of macroeconomics and global geopolitics, being replaced by categories such as globalization, globalization, neoliberalism and empire. Not infrequently, imperialism began to be designed as a military onslaught of one nation over another or, that represents a thought further simplifying, one military action and economic of the United States. Prima facie, all these assumptions appear to be correct, however the study of immanent contradictions to the capital movement and the meaning of capitalist imperialism shows us how insufficient they are. We have as thesis that imperialism, despite attempts of obscuring it through several mystifying expressions, continues to be an indispensable tool for understanding of the contradictory totality of capitalism.The exact comprehension of the contemporary imperialist dynamic represents a Herculean task and not Talmudic, which requires scrutinizing the writings of the early Marxist critics of the phenomenon, located in the II International, transiting by the analysis of Marxist theorists of dependency , the decades of 1960/70, toward the most recent analyzes. The investigations performed through reading the extensive bibliography on the subject, of institutional documents and the reality in different geographical scales allowed to aver our thesis that imperialism is, still, the current phase of capitalism, on this account the recorded changes in this mode of production along the XX century were not able to overcome it. The imperialism intensified its expropriating and wasteful capacity through the formation of an imperialist system on a global scale, which intersects the interests of sundry capitals located in distinct social formations. The known relation among the spoiler imperialist center, formed by a restrict core of nations, and the massive set of subdued peripheral nations, no longer accurately portrays the reality. Regardless the continuity of political-economics hierarchies among the nations, the imperialism can not be explained simply by them. The hegemonic reach of finance capital and the dissemination of its parasitic face, the fictitious capital, urged worldwide interpenetration of purposes among based corporations in numerous countries and states. No longer can determine the boundary of a capital, because its stateless rationality presented itself in clamant way, by means of mergers, associations, joint ventures, cartels and profusion of actions and derivatives. Intensified the primary and secondary expropriations practiced against workers and the rivalries between national bourgeoisies are increasingly blend of the common desire to leverage the profit gather and all social wealth. What allowed us to conclude that contemporary imperialism is more harmful and represents a risk not only to workers, but also to humanity, because it coincides with the time wherein the articulated capital in different scales virulently subtracts the rights, the social wealth and even the elementary means to (re) production of the species.